1988
DOI: 10.1037/0022-3514.54.3.486
|View full text |Cite
|
Sign up to set email alerts
|

The impact of daily stress on health and mood: Psychological and social resources as mediators.

Abstract: This study examined daily stress processes among 75 married couples across 20 assessments during a 6-month period. The somatic and psychological effects of common everyday hassles were investigated. Overall, there was a significant relationship between daily stress and the occurrence of both concurrent and subsequent health problems such as flu, sore throat, headaches, and backaches. The relationship of daily stress to mood disturbance was more complex. The negative effects of stress on mood were limited to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
926
2
9

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,220 publications
(973 citation statements)
references
References 24 publications
36
926
2
9
Order By: Relevance
“…For example, daily stressors have been associated with both concurrent and subsequent health problems [35], and daily negative affect has been associated with engagement in more negative health behaviors [36]. Moreover, higher resting [37] and ambulatory [38] heart rate levels have been shown to predict poor cardiovascular health and mortality.…”
Section: Dynamic Indices Of Healthmentioning
confidence: 99%
“…For example, daily stressors have been associated with both concurrent and subsequent health problems [35], and daily negative affect has been associated with engagement in more negative health behaviors [36]. Moreover, higher resting [37] and ambulatory [38] heart rate levels have been shown to predict poor cardiovascular health and mortality.…”
Section: Dynamic Indices Of Healthmentioning
confidence: 99%
“…There are four subscales: Hassles Frequency (number of events rated as a hassle); Hassles Severity (average severity rating on a 4-point scale for hassles (0 = none or not applicable, 1 = somewhat, 2 = quite a bit, and 3 = a great deal)); Uplifts Frequency (number of events rated as an uplift); and Uplifts Intensity (average intensity rating on 4-point scale for uplifts (0 = none or not applicable, 1 = somewhat, 2 = quite a bit, and 3 = a great deal). This scale has been shown to have both test-retest and internal consistency and concurrent validity (Delongis, 1985;Delongis et al, 1988).…”
Section: Les-mentioning
confidence: 99%
“…Non-specific physical symptoms are regularly experienced by the general population (Rief, Hessel, & Braehler, 2001), and represent a measure of current ongoing physical health below the threshold of disease (Ferguson, Cassaday, Erskind, & Delahaye, 2004). DeLongis and colleagues found that daily stressors influenced both somatic symptoms and mood when measured at the daily level (Delongis, Folkman, & Lazarus, 1988). C has also been investigated in the study of symptom reporting, and evidence suggests that those low on C report the experience of more severe symptoms (Ferguson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%